Prevalência e diversidade de Haemosporida em aves silvestres de diferentes habitats no Brasil e na Venezuela - Nayara de Oliveira Belo (2011)
Environmental changes such as loss and habitat degradation influence the distribution of wild species, which may be an important factor for change in the ecology of pathogen transmission therefore lead to the emergence and proliferation diseases. Brazil has been suffering from an intense and rapid process fragmentation and degradation due to agricultural activities and urbanization. In order to better understand how different types of impacted habitats or not influence the prevalence of infectious diseases in a wild environment, three areas in the Tocantins State, with different environmental characteristics were studied with respect to prevalence and genetic diversity of haemosporidian, Plasmodium spp. and Haemoproteus spp. Therefore, 676 wild birds from three different environments (intact Cerrado, disturbed Cerrado and transition area Amazonian rainforest-Cerrado) were analyzed. We observed a high prevalence of Plasmodium spp./Haemoproteus spp. in the three environments, with an overall infection prevalence of 46%, being 54.7% of infected birds originated from the disturbed Cerrado, 41.4% of intact Cerrado, 50.2% of transition area. Several aspects related to the prevalence of parasitism by Plasmodium spp./Haemoproteus spp. were analyzed, such as the effects of type and habitat preferences, rainy or dry season, the presence of migratory species, molting and feeding guilds. We observed a high prevalence of parasites in birds caught in the woods (56%), and those in birds that attend the open forest (54.5%). A high prevalence also was observed in birds caught in the rainy season (38.7%) among migratory birds (44%) and omnivorous birds (59.2%). Twenty-one parasite lineages were defined from mitochondrial sequences, including 11 Plasmodium lineages and 10 Haemoproteus lineages. The prevalence and diversity of Plasmodium spp. or Haemoproteus spp. were similar among the three habitats studied. However, higher parasite prevalence was detected in birds of the disturbed Cerrado area when compared to those derived from the intact Cerrado area. Fifteen of the parasite lineages had not been previously escribed and might be restricted to these habitats or to the Tocantins region. Six haemosporidian lineages previously known from other regions, particularly the Caribbean Basin, comprised 50-80% of infections in each of the samples, indicating a regional relationship between distribution and parasite abundance. Thus, it was also determined by comparative analysis, the parasite prevalence and diversity in birds from an arid zone of Venezuela. High prevalence ofhaemoparasites (41%) was detected for this region and nine new lineages were first described. Five Brazilian lineages were shared with five Venezuela lineages, being six Plasmodium VIII lineages and four Haemoproteus lineages. These lineages shared between Brazil andVenezuela are not restricted to a particular host and often occur in different regions of the world. Possibly these lineages are generalist lineages. In order to better understand the relationship between landscape and avian malaria parasites it is necessary to perform more studies in different habitat types that comprise the ecosystems of Brazilian and Venezuelan regions